Robustness Evaluation of Gaming Performance Against Input Rate Variations in Procedurally Generated Roguelike on Godot Engine: Evaluasi Robustness Performa Game Roguelike terhadap Variasi Input Rate Menggunakan Monkey Testing pada Godot Engine - Santoso, Rizky Aji; Rosyid, Harits Ar (Academia Open, 2026)
General Background: System resilience under high interaction frequency is essential for maintaining real-time game stability. Specific Background: This study evaluates the Dodge and Deflect roguelike game on Godot Engine 4.4.1 using Monkey Testing with controlled input rate variation in a low-end virtual environment. Knowledge Gap: Quantitative analysis of input intensity on engine stability remains limited compared to playability-focused studies. Aims: This study aims to identify performance degradation patterns and critical stability thresholds driven by input rate escalation. Results: A strong negative correlation (r = -0.93) is found between input intensity and system stability, with performance declining from Level 11 to Level 4 under extreme conditions, accompanied by FPS drops and increased freeze events, while memory usage remains stable. Novelty: The study applies controlled Monkey Testing to isolate input rate as the main stress factor in a procedurally generated roguelike setting. Implications: The findings provide an empirical basis for optimizing event handling and defining minimum system requirements. Highlights• Inverse pattern between interaction density and system endurance• Failure threshold identified through reduced progression capability• Processing constraints emerge as dominant limitation under stress KeywordsMonkey Testing; Godot Engine; Input Rate; Performance Degradation; Game Robustness